Prevalence, Risk Factors and Outcomes of Pregnancies with Small for Gestational Age Fetus at BPKIHS - Shrestha, Ramesh; Bhandari, Sangeeta; Basnet, Pritha; Manandhar, Tara; Thapa, Baburam Dixit; Shrestha, Sapana; Kafle, Shyam Prasad (Birat Journal of Health Sciences, 2020)
Introduction: Small-for-gestational-age (SGA) is defined by a birth weight below the 10th percentile for mean weight corrected for gestational age. It is associated with adverse health events throughout life, including substantial perinatal morbidity and mortality rates. Objectives: The aims of the study was to estimate the prevalence of the SGA newborns, attributable factors for SGA and perinatal outcomes of SGA. Methodology: A hospital based prospective cohort study was conducted among pregnant women after 28 weeks' gestational age in the Department of Obstetrics and Gynaecology, BPKIHS, Dharan from October, 2016 to June, 2017.A total of 150 study population was sampled using purposive sampling technique whose symphysio-fundal height lags the gestational age by four cms. The association for risk factors between the various socio-demographic parameters and SGA was analysed using chi-square test for categorical data and t-Test for continuous data with p value<0.05 considered as significant. The mothers and babies were followed up till discharge from the hospital for outcomes. Result: There was a total of 140 SGA with 10 appropriate for gestational age (AGA) fetuses among 6,500 hospital deliveries above 28 weeks' gestation, hence the prevalence was 2.15%. The risk factors for very small for gestational age were history of birth of SGA fetus (OR, 1.25; 95% CI, 1.15-1.35); history of recurrent pregnancy loss (OR, 1.25; 95% CI, 1.15-1.35); personal history of substances abuse in the index pregnancy (OR, 1.68; 95% CI, 1.47-1.92); adverse obstetrics or medical events in the index pregnancy (OR, 2.21; 95% CI, 1.10-4.45); high blood pressure at admission (OR, 1.58; 95% CI, 1.96- 2.59) and significant urinary proteinuria (OR, 2.26; 95% CI, 1.00-5.09).SGA newborns correlated with increased risk of operative delivery and adverse perinatal outcomes, including oligohydramnios, low Apgar scores, resuscitation at birth, admission to the neonatal intensive care unit or nursery, metabolic complications and fetal death. Conclusions: SGA have distinct modifiable risk factors and mortality patterns suggesting potential implications for public health and urgent need to intervene with effective interventions.